All the madwomen in the attic: alienation and culture shock in Jamaica Kincaid’s See Now Then = Todas las locas del ático: alienación y shock cultural en See Now Then, de Jamaica Kincaid - Alonso Alonso, María (Estudios Humanísticos. Filología, 2018)
Este artículo analiza la última novela de Jamaica Kincaid, See Now Then. Después de ofrecer una contextualización y de acuerdo con el marco teórico que articula el análisis, esta aproximación tomará como referencia dos clásicos de la literatura inglesa como son Jane Eyre de Charlotte Brontë y Wide Sargasso Sea de Jean Rhys para explorar cuestiones de alienación y shock cultural a través de la prosa compleja y barroca que caracteriza los trabajos de Kincaid. This article analyses Jamaica Kincaid’s latest novel, See Now Then. After contextualising the text and according to the theoretical framework that structures this analysis, this approach will consider two classics of English literature such as Charlotte Brontë’s Jane Eyre and Jean Rhys’s Wide Sargasso Sea to explore issues of alienation and culture shock through the highly complex and baroque prose that characterises Kincaid’s works.